Peste des Petits Ruminant: Exotic Ruminant Disease That Should Be Anticipated - Indrawati Sendow; Adjid RMA; NLPI Dharmayanti (Indonesian Center for Animal Research and Development, 2014)
Peste des Pettits Ruminants (PPR) is one of infectious and contagious viral diseases from morbilliviruses group in ruminants especially small ruminants. The disease was characterized by nasal and eye discharge, conjunctivitis, high fever, gastrointestinal disorder and pneumonia. Hence PPR may cause economical impact for the farmers due to the decrease of animal productivity and death. Peste des pettits ruminants is also a disease that has serious attention on the Office International des Epizooties (OIE) list. In Indonesia, the disease has not been reported, so the anticipation of entering the disease is needed. The paper will describe the disease in many aspects included transmission, host ranges, epidemiology, clinical disease, diagnosis and the ability to identify the disease in Indonesia. Key words: Peste des Pettits Ruminants, epidemiology, diagnose, ruminants